2013
DOI: 10.3390/agriculture3010170
|View full text |Cite
|
Sign up to set email alerts
|

Potential Nutritional Benefits of Current Citrus Consumption

Abstract: Citrus contains nutrients and phytochemicals that may be beneficial for health. We collected citrus production and consumption data and estimated the amount of these compounds that are consumed. We then compared the amounts of citrus and citrus-derived compounds used in studies that suggest a health benefit to the amounts typically found in citrus. Data is scarce, but suggests that citrus consumption might improve indices of antioxidant status, and possibly cardiovascular health and insulin sensitivity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 81 publications
0
77
0
4
Order By: Relevance
“…Moreover, citrus peels are rich source of vitamins A, C, and folic acid and some phytochemical compounds such as limonoids, coumarins and carotenoids (Di Majo et al, ; Turner & Burri, ). Many studies showed the considerable bactericidal activity and inhibitory effects of grapefruit peel extract against several gram‐positive and gram‐negative bacterial isolates (Negi & Jayaprakasha, ; Okunowo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, citrus peels are rich source of vitamins A, C, and folic acid and some phytochemical compounds such as limonoids, coumarins and carotenoids (Di Majo et al, ; Turner & Burri, ). Many studies showed the considerable bactericidal activity and inhibitory effects of grapefruit peel extract against several gram‐positive and gram‐negative bacterial isolates (Negi & Jayaprakasha, ; Okunowo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Citrus is popular for its characteristic flavor, taste, aroma, higher content of vitamin C, phenolics, and other nutritional benefits (Anonymous, ; Jandric, Islam, Singh, & Cannavan, ). Wider range of citrus variety is present worldwide such as sweet oranges ( C. sinensis ), mandarins ( C. unshi , C. tangerine, reticulate , C. clementine ), sour/bitter oranges (Seville, C. aurantium ), lemons ( C. limon ), limes ( C. aurantifolia and latifolia ), grapefruit ( C. paradisi ), and pummelos ( C. grandis ) (Turner & Burri, ). There are three kinds of citrus produced in India viz Mandarin (Kinnow, Nagpur, Coorg, and Khasi), Sweet orange (Mosambi, Jaffa, Malta, and Satgudi) and lime/lemon which has commercial importance and cultivated round the country.…”
Section: Introductionmentioning
confidence: 99%
“…Healthy properties of sweet orange [Citrus sinensis (L.) Osbeck] derive from a synergistic effect among constituents of the endocarp edible compartments, including both structural primary metabolites and a broad range of secondary phytochemicals (Turner & Burri, 2013). In the hesperidium a complex system of membranes (juice sacs and segments) and spongy pectinous cells (albedo and fruit core) envelop the juice fraction where most phenolic and carotenoid phytonutrients are retained along with sugars, organic acids, pectins, lipids and mineral compounds (U.S. Department of Agriculture, 1956).…”
Section: Introductionmentioning
confidence: 99%